Analysis of referral appropriateness in the Western Cape, South Africa, and implications for resource allocation - David B. Richards; Gabrielle A. Jacquet (African Journal of Emergency Medicine, 2012)
Introduction: The public health system in South Africa is a tiered system. Throughout the Western Cape are Community Health Centers (CHCs), which serve as the entry point for the majority of patients seeking medical care. Patients who require urgent or emergent treatment at the CHCs are transferred to secondary hospitals for further care. Patients requiring the highest level of care, such as specialized radiology or sub-specialist care are then transferred to a tertiary hospital. Hypothesis: Addressable limitations of basic human and technical capacities lead to preventable transfers and treatment delays for patients seeking care in this system. Methods: Over a six-week period in 2006, 270 charts from patients transferred from one of five CHCs to a secondary hospital were reviewed to uncover addressable human and technical limitations that may have led to transfer. Results: Of approximately 61950 patients seen at the CHCs during the study period 270 were transferred. 22% (60/270) of these met criteria as possibly unnecessary transfers. Of these, 47% (28/60) were transferred for radiograph interpretation, 23% (14/60) were transferred for ultrasound, and 17% (10/60) were transferred for incision and drainage. 13% (8/60) were transferred for a variety of reasons but then were immediately transferred onward to a tertiary care center. Discussion: 22% (60/270) of transfers could have been avoided if specific resources or training were available to CHCs or if patients requiring tertiary care were identified prior to transfer to a secondary facility. The next step will be to compare the cost of providing these resources to the savings from decreased patient transfers. We believe the techniques used in this study can serve as a model for efficiency assessment of tiered health care systems throughout South Africa and beyond.